Medial Extension of Medial Sphenoid Wing Meningioma from the Anterior Clinoid Line: Does It Truly Affect the Surgical Outcome? - Arab, Ala; Hawsawi, Aysha; Bafaquh, Mohammed; Orz, Yasser; AlYamany, Mahmoud; Alobaid, Abdullah (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background Medial sphenoid wing meningiomas (MSWMs) account for approximately 20% of all meningiomas that are known for their critical relation to neurovasculture structures.Objective The purpose of this study is to examine the relation between the maximum diameter of the MSWM medial to the anterior clinoidal line (AC line) and surgical outcome.Methods This is a retrospective cohort study investigating all surgically resected MSWM cases at our institution over 10 years. The patients were divided into groups A and B based on the average ratio between the maximum medial extension of the MSWM from the AC line to the maximum diameter of the tumor, that is, value I = 0.42 (group A ≤ 0.42 and group B > 0.42). And into groups C and D based on the average medial extension of the tumor, that is, 14 mm (group C ≤ and D group D > 14 mm). These measurements were correlated with patients' demographics, preoperative symptoms, and postoperative assessment.Results Among 150 patients, 51patients had MSWM that fulfilled the inclusion criteria. Among them, 76.47% were females with a median age of 48 years (standard deviation [SD] = 47.75 ± 15.11). Also, 92% of the cases were World Health Organization (WHO) grade I. The follow-up period was 0.5 to 10 years. Among them, 40% of group C had gross total resection (GTR), whereas 43% in group D. In group B, 70% had GTR, whereas 48% had GTR in group A. None of the patients developed statistically significant postoperative complications. There is no statistically significant difference in the risk complication with medial extension in all groups.Conclusion The degree of medial extension of MSWM from the AC line has no statistically significant correlation with major postoperative complications, extent of resection, or clinical outcome.
Keywords: sphenoid wing; meningioma; outcome; anterior clinoid line